1968
DOI: 10.1182/blood.v32.6.935.935
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Ultrastructural Localization of Myeloperoxidase in Human Neutrophil and Rabbit Heterophil and Eosinophil Leukocytes

Abstract: Ultrastructural cytochemical observations revealed peroxidase reactivity in primary (azurophil) granules, but not in secondary (specific) granules, of rabbit and human polymorphonuclear leukocytes. Peroxidase reactivity was also observed in the rough endoplasmic reticulum and granules of rabbit eosinophils and in granules of human monocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
1

Year Published

1970
1970
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(27 citation statements)
references
References 6 publications
3
23
1
Order By: Relevance
“…In polymorphonuclear leukocytes the first step in cyanide formation is oxidative chlorination of glycine or other amino acids by the enzyme myeloperoxidase. This enzyme is contained in azurophil granules in the cytoplasm of resting leukocytes (Dunn et al, 1968;Bainton and Farquhar, 1968) but is released into the phagocytic vacuole during phagocytosis (Klebanoff, 1970). Based on results in rat brain fractions, neural tissue may similarly have a cyanide-generating system contained mainly in a subcellular particle that sediments with mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…In polymorphonuclear leukocytes the first step in cyanide formation is oxidative chlorination of glycine or other amino acids by the enzyme myeloperoxidase. This enzyme is contained in azurophil granules in the cytoplasm of resting leukocytes (Dunn et al, 1968;Bainton and Farquhar, 1968) but is released into the phagocytic vacuole during phagocytosis (Klebanoff, 1970). Based on results in rat brain fractions, neural tissue may similarly have a cyanide-generating system contained mainly in a subcellular particle that sediments with mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructurally, these granules contain a central crystalloid (Breton-Gorius, 1966;Hudson, 1966a;Wetzel et al, 1967a;Scott and Horn, 1970), which consists of a highly basic protein that is helminthotoxic and responsible for the eosinophilia of the granules (Horn and Spicer, 1964;Dunn and Spicer, 1969;Olsson et al, 1977;Lewis et al, 1978;Gleich et al, 1980). The granule matrix surrounding the crystalloid contains peroxidase, acid phosphatase, and other hydrolytic enzymes (Wetzel et al, 196713;Dunn et al, 1968;Miller and Herzog, 1969;Bainton and Farquhar, 1970;Bass et al, 1981) and demonstrates cytochemical affinity for uranyl acetate (Hudson, 1967) and phos-photungstic acid (Hudson, 1966b). Early eosinophils (promyelocyte-myelocyte) in marrow specimens contain several basophilic granules (Dunn and Spicer, 1969).…”
mentioning
confidence: 99%
“…Early eosinophils (promyelocyte-myelocyte) in marrow specimens contain several basophilic granules (Dunn and Spicer, 1969). Ultrastructurally these latter granules lack crystalloids but contain lysosomal enzymes similar to those seen in eosinophil crystalloid granules (Wetzel et al, 1967b;Fedorko, 1968;Dunn et al, 1968;Bainton and Farquhar, 1970). The presence of transition forms from granules lacking crystalloids to those containing crystalloids (Hudson, 1966a;Wetzel et al, 1967a) has indicated that the crystalloid-free basophilic granules represent an immature form of crystalloid granules.…”
mentioning
confidence: 99%
“…In contrast, when the buffy coat was treated by method I , all blasts were unreactive (Fig 5 ) . Rare neutrophil promyelocytes showed a positive reaction in the perinuclear space, ER, Golgi zone and azurophil granules as in normal marrow promyelocytes synthesizing myeloperoxidase (Ackerman & Clark, 1971;Bainton et al, 1971;Breton-Gorius & Guichard, 1969;Dunn et al, 1968;Breton-Gorius & Reyes, 1976b). As stated above, the majority of blast cells, fixed with diluted aldehydes (method 2) contained a peroxidase-like activity.…”
Section: Cytochemical and Electron Microscopic Studymentioning
confidence: 69%